OP0150 3-Bromopyruvate Ameliorates Autoimmune Arthritis by Exerting A Dual Effect on Both Th17 and Treg Cell Differentiation and Dendritic Cell Activation. (15th July 2016) - Okano, T.; Saegusa, J.; Nishimura, K.; Takahashi, S.; Sendo, S.; Ueda, Y.; Onishi, A.; Morinobu, A.
Abstract : Background: Recent studies have shown that cellular metabolism plays an important role in regulating immune cell function. In the process of cell differentiation, both interleukin-17-producing T (Th17) cells and dendritic cells (DCs) show increase of glycolytic activity by upregulating glycolytic enzymes, such as hexokinase-II (HK-II). Blocking glycolysis by 2-deoxyglucose has recently been demonstrated to inhibit Th17 cell differentiation while promote regulatory T (Treg) cell generation, and then ameliorate experimental autoimmune encephalitis model. Objectives: The aim of this study is to verify the effect of 3-bromopyruvate (BrPA), a specific inhibitor of HK-II, on the differentiation and function of immune cells and on experimental arthritis in SKG mice. Methods: Arthritis was induced in SKG mice by Zymosan A injection. BrPA (5 mg/kg) was administered subcutaneously once daily. CD4+ T cells from splenocytes of unimmunized SKG mice were cultured with anti-CD3/anti-CD28, anti-IFN-γ, anti-IL-4, IL-6, TGF-β, and IL-2, with or without BrPA for 5 days, and then analyzed by flow cytometry. Bone marrow (BM) cells from unimmunized SKG mice were cultured with GM-CSF and IL-4 (for 3 days), and with LPS (for 1 day) with or without BrPA, and then analyzed by flow cytometry. Results: Treatment with BrPA significantly ameliorated arthritis of SKG mice (Figure ). Histological scores of arthritis in BrPA-treated mice were significantly reduced compared with those in control mice. Flow cytometric analysis revealed that significant increase of Treg cells, decrease of Th17 cells, and decrease of CD40+CD86+CD11b+CD11c+ activated DCs were observed in the splenocytes from BrPA-treated mice. BrPA did not affect IFN-γ-producing Th1 cells nor IL-4-producing Th2 cells. In vitro, BrPA facilitated the differentiation of Treg cells, while it inhibited the development of Th17 cells. In addition, treatment of BM cells with BrPA inhibited the differentiation of activated DCs and the production of TNF-α and IL-6 from DCs. Conclusions: BrPA facilitates the differentiation of Treg cells, and inhibits the development of Th17 cells and the activation of DCs, and ameliorates arthritis in the SKG mice. Disclosure of Interest: None declared